Can Cultural Intelligence Affect Employee’s Innovative Behavior? Evidence From Chinese Migrant Workers in South Korea - Fan, Peng; Song, Yixiao; Nepal, Surya; Lee, HyoungTaek (Frontiers in Psychology, 2020)
This empirical study explores the effect of cultural intelligence (CQ) on migrant workers’ innovative behavior as well as the mediating role of knowledge sharing on the CQ-innovative behavior relationship. Besides, it also examines the extent to which the mediating process is moderated by climate for inclusion. Using survey data collected from Chinese migrant workers and their supervisors working in South Korea (n=386), migrant workers’ CQ is found to positively impact their innovative behavior through enhanced knowledge sharing. However, it is observed that, this indirect relationship is significant, only for migrant workers in a strong climate for inclusion. Thus, these findings reveal the underlying mediation and moderation mechanism, and consequently unveil the important role of migrant workers’ CQ in shaping their behavior. This study provides insightful and practical implications to a multi-cultural organization, where culturally diverse migrant workers work together.